EKSPLORASI PEMBELAJARAN MATEMATIKA BERBASIS BUDAYA LOKAL AMMATOA SUKU KAJANG - Satriani, Sri (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2024)
This type of research is an exploratory qualitative research that aims to: explore teacher and student activities and student learning outcomes in culture-based mathematics learning. The instruments used are 1) teacher and student activity observation sheets, 2) interviews, and 3) learning outcome tests. The subjects in the study were fifth-grade students of SDN 351 Ammatoa Traditional Area taking 2 groups for in-depth observation, namely the Kajang Dalam group and the Kajang Luar group. From the 2 groups, 1 person from each group was taken for in-depth interviews. The results showed that: 1) teachers' activities in learning mathematics based on Ammatoa local culture were by the expected learning objectives; 2) student activities from both Kajang Dalam and Kajang luar  related to Pasang Ri Kajang values have generally been seen during the learning process although, at the beginning of the meeting, students from the Kajang Luar group still did not reflect the value of tallang sipahua manyu'siparampe and a'lemo sibatu a'bulo sipappa when working in groups, whereas the Kajang Dalam group has reflected these values in their activities from the beginning to the end of the meeting, 3) the learning outcomes of students from both Kajang Luar and Kajang  Dalam after the implementation of Ammatoa local culture-based mathematics learning has increased